State Actions to Ban Gender-Affirming Care for Minors and the Ways Forward - Libertella, Ali (Columbia Journal of Gender and Law, 2024)
As of October 2023, twenty-one states have passed laws that ban medically necessary gender-affirming care to minors. This Note will discuss the actions of three such states—Texas, Florida, and Arkansas—in 2022.2 These state actions demonstrate three different ways in which states have restricted access to medically necessary gender-affirming care. To move forward, lawyers and advocates must continue to litigate against these bans, state legislatures should enact sanctuary statutes protecting trans youths’ access to gender-affirming care, and the U.S. Food & Drug Administration (FDA) should make medications—including puberty blockers and hormones—available on-label and across state lines through Telehealth. It is important to recognize that disapproving parents pose insurmountable barrier to minors’ self-realization, exploration of their genders, and access to care. There is abundant legal scholarship on parental consent in this context and analogous ones, such as the mature minor doctrine that concerns minors accessing abortion and reproductive care like birth control. However, this Note focuses solely on situations in which transgender youths’ parents support their children’s identities and allow them to receive gender-affirming care. When a state has a ban on gender-affirming care, parents’ consent would not matter in the face of such a ban, unless the family is financially able and willing to move to a state allowing access to such care.